Nanoparticles technology promoting strategies for cancer therapy: Review - Abdalsamed, Ihssin; Amar, Ibrahim; Ahwidi, Mohammed; Abrika, Omar; Ali, Masood (Libyan Journal of Science &Technology, 2022)
Cancer is the most serious disease in the world and has been considered as the first fatal disease to the humankind as its incidence rates continue to increase rapidly worldwide. Chemotherapy, Radiation therapy, Immunotherapy and Hyperthermia are the most common treatments for cancer in developed countries, while surgical operations are used in undeveloped countries, which have been found to cause negative side effect on human health. Recently, Nano treatment is used to cure a number of cancer cases, which have shown significant results than surgical operations. Such success has encouraged scientists and researchers to develop Nanotechnological devices named as nanoparticles (NPs) which have become one of the greatest medical healthcare settings as they provide potential benefits for diagnosing and treating metastatic cancer, such as a tumor. On other hand, nanoparticles improved the ability to delivery drugs to the major sites of metastasis without effecting noncancerous cells. Moreover, beside reported nanoparticles (NPs) have significant to escape antibody and extravasate into the tumor cells. In this review, we focus and outline on Nanodevice types: Quantum dots (QDs), Nanogold shell (AuNPs), Dendrimers, Nanopore, and Nanotubes for their principles, applications, operation processes and their recent highlights in cancer research area are also considered in this paper. Finally, we provide some perspectives on the future challenges and development of drug delivery systems.